Consumption of health and social resources by people with persistent COVID and its relationship with persistent symptomatology: A descriptive and correlational study. - Lafita-Mainz, Sergio; Oliván, Diego; Martínez-Pecharroman, Maria del Mar; Refusta-Ainaga, Raquel; Blasco-González, Isabel (Acciones e Investigaciones Sociales, 2023)
Introduction: Approximately 10% of patients who have been infected with SARS-COV-2 have persistent symptoms that have reduced their quality of life. This is especially relevant in people who were infected during the first wave. The aim of this study is to analyze the consumption of health and social resources by people with persistent COVID and its relationship with the persistent symptomatology they present. Methodology: Cross-sectional descriptive and correlational study in which data are collected from patients with persistent COVID collecting sociodemographic, clinical variables (number of persistent symptoms), and consumption of health and social resources. A descriptive and correlational study was performed. Results: The participants in this study show a high affectation reflected in the large number of residual symptoms they present (mean 16.47 symptoms). Therefore, there is a considerable increase in the use of public and private health, social and legal resources. Primary care services are the most frequently used by these patients. Conclusion: Timely planning of patient-centered resources and services for post-COVID-19 care is needed.